THE EFFECT OF GOVERNMENTAL LAWS AND PHARMACEUTICAL ETHICS ON BUILDING A DISTINCTIVE RELATIONSHIP BETWEEN PHARMACISTS AND THEIR CUSTOMERS - ABDELMALEK (ABUJARAD ALHUWITAT), MAYSOON (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: This study aimed to investigate the effect of governmental laws and pharmaceutical ethics on building a distinctive relationship between pharmacists and their customers from the perspective of pharmacists in Jordan through measuring the customers’ satisfaction and their perceived value. Methods: This study is a descriptive and correlative one. A self-administrated questionnaire was distributed to a random sample of 110 pharmacists working in private pharmacies to measure the effect of governmental laws and pharmaceutical ethics on building a distinctive relationship between pharmacists and customers. Results: ANOVA-test showed a significant effect of governmental laws and pharmaceutical ethics on building a distinctive relationship between pharmacists and their customers (p = 0.003) and on the customer–perceived value (p = 0.00). Multiple regression analysis showed a significant effect of the application of ethical standards on building a distinctive relationship between pharmacists and their customers (p = 0.006) and a significant effect of both dimensions: (application of laws and regulations) and (application of ethical standards) on customer–perceived value (p = 0.004, p = 0.009) respectively. Moreover, there was a statistically significant effect of the application of ethical standards on customers’ satisfaction (p = 0.03). Conclusion: Based on the results of this study, there should be an effort by the government and the private institutions responsible for the pharmacy profession in Jordan to contribute to build a distinctive relationship between pharmacies and their customers, as this relationship increases the perceived value and satisfaction of customers.